2013
DOI: 10.1111/jnc.12522
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor progression locus 2 protein kinase in glial inflammatory response

Abstract: Tumor progression locus 2 (Tpl2)/Cot kinase is a newer member of MAP3K family that is now known for its essential role in TNFα expression in macrophages, but its proinflammatory signaling, if any, in glia is unknown. When cultures of murine microglia and astrocytes were exposed to lipopolysaccharide, there was a rapid activation (i.e., phosphorylation) of Tpl2 in parallel to the activation of down-stream effector MAPKs i.e., ERK, p38 MAPK and JNK. Pre-incubation of the cultures with a Tpl2 inhibitor selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(80 reference statements)
0
6
0
Order By: Relevance
“… 22 In addition to ERK1/2, we showed that Tpl2 engaged the signaling kinases JNK and p38 in β -cells, as reported in microglial cells treated with LPS. 28 This differs from MEF cells 20 , 21 and macrophages 20 stimulated with TNF- α where either only ERK1/2 and JNK or ERK1/2 and p38 are dependent on Tpl2, respectively. In β -cells and in rodent islets, the activation of ERK1/2, p38 MAPK, JNK and/or NF- κ B pathways have been proposed to play roles in cytokine-induced iNOS production, apoptosis and altered insulin secretion.…”
Section: Discussionmentioning
confidence: 89%
“… 22 In addition to ERK1/2, we showed that Tpl2 engaged the signaling kinases JNK and p38 in β -cells, as reported in microglial cells treated with LPS. 28 This differs from MEF cells 20 , 21 and macrophages 20 stimulated with TNF- α where either only ERK1/2 and JNK or ERK1/2 and p38 are dependent on Tpl2, respectively. In β -cells and in rodent islets, the activation of ERK1/2, p38 MAPK, JNK and/or NF- κ B pathways have been proposed to play roles in cytokine-induced iNOS production, apoptosis and altered insulin secretion.…”
Section: Discussionmentioning
confidence: 89%
“…Chronic inflammation plays a critical role in the development of obesity‐related metabolic diseases, and TPL2 is an important mediator of nuclear factor kappa B (NF‐κB) and MAPK signaling and the related inflammatory responses . These interactions suggest the possibility of a close relationship between inflammatory regulation by TPL2 and its influence on hepatic steatosis (HS).…”
Section: Resultsmentioning
confidence: 99%
“…Chronic inflammation plays a critical role in the development of obesity-related metabolic diseases, (27) and TPL2 is an important mediator of nuclear factor kappa B (NF-jB) and MAPK signaling and the related inflammatory responses. (17,28) These interactions suggest the possibility of a close relationship between inflammatory regulation by TPL2 and its influence on hepatic steatosis (HS). TPL2-HKO mice had higher serum levels of the anti-inflammatory factor, interleukin (IL)-10, and lower serum levels of proinflammatory markers, including tumor necrosis factor alpha (TNF-a), IL-1b, monocyte chemoattractant protein 1 (MCP-1), and IL-6, compared to TPL2-flox controls after 12 weeks on an HFD (Fig.…”
Section: Deletion Of Tpl2 In Hepatocytes Ameliorates Hfd-induced Obesmentioning
confidence: 99%
“…TPL2 is involved in numerous intracellular signaling pathways, with a prominent role in the regulation of inflammatory signal transduction ( 2 6 ). TPL2 may be able to engage a plethora of signaling pathways and to act in concert with other kinases and signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification of prognostic markers and novel therapeutic targets is of crucial importance. The serine/threonine protein kinase tumor progression locus 2 [TPL2/MAP3 kinase 8 (MAP3K8)] acts as an essential signal for the expression of pro-inflammatory mediators in several cell systems, including peripheral macrophages ( 2 ), adipocytes ( 3 ), hepatic stellate cells ( 4 ), airway epithelial cells ( 5 ) and glial cells ( 6 ). Inflammatory molecules have emerged as significant in the development of cancer, with roles in events leading to the formation, growth and metastasis of tumors.…”
Section: Introductionmentioning
confidence: 99%